The knowledge nurses about diab - Kadłubowska, Monika; Bąk, Ewelina; Kolonko, Jolanta (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. During the last years the prevalence of diabetes mellitus has increased systematically. The number of people suffering from diabetes worldwide is expected to reach 300 million in 2010.Most patients develop diabetic complications: retinopathy, nephropathy, and neuropathy. Diabetes and its complications impair patients’ quality of life and impose signifficant economic burden. Diabetes is considered one of the most challenging health problems in the 21st century. Implementing continuing nursing education programs will result in improved diabetes care, reduced rate of complicatons, and decreased cost of treatment. The aim of the study. Assess the nurses’ knowledge about diabetes. Material and methods. The study was conducted among 60 nurses from Hospital in Bielsko-Biala between November 2007 and January 2008 using a questionnaire survey technique. Results. The results of our study show that the nurses’ knowledge about diabetes is unsufficient, what may unfavourably influence their nursing work. The main reasons for lack of motivation among nurses to improve their education are unavailability of educational materials and high costs of training.